Existence of viable Mycobacterium leprae in natural environment and its genetic profiling in a leprosy endemic region - Turankar, Ravindra P.; Singh, Vikram; Lavania, Mallika; Singh, Itu; Sengupta, Utpal; Jadhav, Rupendra S. (Frontiers in Tropical Diseases, 2022)
Introduction: Molecular epidemiology of leprosy is very important to study leprosy transmission dynamics and to enhance our understanding of leprosy in endemic areas by utilizing the molecular typing method. Nowadays our understanding of leprosy transmission dynamics has been refined by SNP typing and VNTR marker analysis of M. leprae strains. Objective: This study was carried out to find out the presence of viable M. leprae in the soil and water samples from residing areas of leprosy patients staying in different blocks of Purulia district of West Bengal, understanding their genotypes and compared with that of M. leprae present in patients. Material and methods: Slit-skin smear (SSS) samples(n=112) were collected from the active multibacillary leprosy patients from different blocks of leprosy endemic area. Soil samples (n=1060) and water samples (n=620) were collected from residing areas of leprosy patients. SNP subtyping was performed by PCR followed by sequencing. Multiplex PCR was performed using fifteen ML-VNTR loci and results were analysed. Results: We observed high PCR positivity in soil samples (344 out of 1060; 32%) and water samples (140 out of 620; 23%). These PCR positive samples when further screened for viability, it was observed that 150 soil samples (44%) and 56 water samples (40%) showed presence of 16S rRNA. SNP typing of M. leprae revealed presence of predominantly type 1. SNP subtype 1D (83%) was most prevalent in all the blocks of Purulia followed by subtype 1C (15%) and subtype 1A (2%). SNP subtype 2F was noted in only one sample. SNP and VNTR combination showed presence of similar strain type in certain pockets of Purulia region which was responsible for transmission. Conclusion: Presence of viable M. leprae in the environment, and presence of SNP Type 1 M. leprae in patients and environment suggests both environment and patients play a role in disease transmission.